IMPLEMENTASI METODE DEMONSTRASI MATA KULIAH DESAIN DAN PERENCANAAN PEMBELAJARAN PAI PADA MATERI PENYUSUNAN RENCANA PELAKSANAAN PEMBELAJARAN PAI DI UNIVERSITAS NAHDALTUL ULAMA - Wahyuni, Sri; Ftirianingsih, Dwi (Mozaic : Islam Nusantara, 2023)
Learning methods are one of the important reasons for achieving learning objectives. One of the requirements to become a professional teacher is to be able to compile a lesson implementation plan; therefore, the selection of the right learning method to teach students about how to compile a learning implementation plan must really be considered. This research is intended to provide an overview of the implementation of the application of demonstration methods in design courses and learning strategies, along with material for preparing learning implementation plans for students of the Islamic Education study program in the fourth semester of UNUSIA. The preparation of research uses a descriptive-qualitative approach; data is collected by observation, interviews, and documentation. Furthermore, the analysis technique uses the Miles and Huberman technique, which is to summarize data, present data, and provide conclusions. The findings of the implementation of this demonstration method are: theoretical discussions on matters related to PAI learning planning; secondly, providing examples or practicing the process of preparing PAI learning implementation plans; and third, simulation and evaluation. .